Melatonin regulates angiogenic factors under hypoxia in breast cancer cell lines - Jardim-Perassi, Bruna Victorasso; Lourenço, Mateus Repolês; Doho, Gabriel Mandarini; Grígolo, Ingrid Helen; Gelaleti, Gabriela Bottaro [UNESP]; Ferreira, Lívia Carvalho [UNESP]; Borin, Thaiz Ferraz; Moschetta, Marina Gobbe; de Campos Zuccari, Debora Aparecida Pires (My University, 2016)
Angiogenesis is the process of new blood vessel formation, regulated by a number of pro- and antiangiogenic factors and usually begins in response to hypoxia. Exogenous administration of melatonin has shown numerous anti-tumor effects and appears to inhibit tumor angiogenesis. However, many factors involved in the anti-angiogenic effect of melatonin are still under investigation. Here, we evaluate the effects of melatonin on cell viability and expression of angiogenic factors in MCF-7 and MDA-MB-231 breast cancer cells under hypoxic conditions. Cell viability was investigated by MTT and gene and protein expression of the hypoxia-inducible factor-1a (HIF-1α) and vascular endothelial growth factor (VEGF-A) were verified by qPCR and immunocytochemistry after melatonin treatment (1 mM) under hypoxic conditions. Additionally, a protein array with 20 different cytokines/factors was performed on tumor cell lysates. The results showed that 1 mM of melatonin reduced the viability of MCF-7 and MDA-MB-231 cells (p < .05). This treatment also decreased both gene and protein expression of HIF-1a and VEGF-A under hypoxic conditions (p < .05). Among the proteins evaluated by protein array, melatonin treatment during hypoxia reduced VEGF-C, VEGFR receptors (VEGFR2 and VEGFR3), matrix metalloproteinase 9 (MMP9) and Angiogenin in MCF-7 cells. In MDA-MB-231 cells, a significant decrease was observed in VEGFR2, epidermal growth factor receptor (EGFR) and Angiogenin (p < .05). Taken together, these results showed that melatonin acts in the regulation of angiogenic factors in breast tumor cells and suggests an anti-angiogenic activity, particularly under hypoxic conditions.
Keywords: Angiogenesis; Breast neoplasms; Cell hypoxia; Cell line; Gene expression; Melatonin; Vascular endothelial growth factors